-2x+1-(-3x+3)=-4+(x-2)

Simple and best practice solution for -2x+1-(-3x+3)=-4+(x-2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2x+1-(-3x+3)=-4+(x-2) equation:


Simplifying
-2x + 1 + -1(-3x + 3) = -4 + (x + -2)

Reorder the terms:
-2x + 1 + -1(3 + -3x) = -4 + (x + -2)
-2x + 1 + (3 * -1 + -3x * -1) = -4 + (x + -2)
-2x + 1 + (-3 + 3x) = -4 + (x + -2)

Reorder the terms:
1 + -3 + -2x + 3x = -4 + (x + -2)

Combine like terms: 1 + -3 = -2
-2 + -2x + 3x = -4 + (x + -2)

Combine like terms: -2x + 3x = 1x
-2 + 1x = -4 + (x + -2)

Reorder the terms:
-2 + 1x = -4 + (-2 + x)

Remove parenthesis around (-2 + x)
-2 + 1x = -4 + -2 + x

Combine like terms: -4 + -2 = -6
-2 + 1x = -6 + x

Solving
-2 + 1x = -6 + x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1x' to each side of the equation.
-2 + 1x + -1x = -6 + x + -1x

Combine like terms: 1x + -1x = 0
-2 + 0 = -6 + x + -1x
-2 = -6 + x + -1x

Combine like terms: x + -1x = 0
-2 = -6 + 0
-2 = -6

Add '2' to each side of the equation.
-2 + 2 = -6 + 2

Combine like terms: -2 + 2 = 0
0 = -6 + 2

Combine like terms: -6 + 2 = -4
0 = -4

Simplifying
0 = -4

Combine like terms: 0 + 4 = 4
4 = -4 + 4

Combine like terms: -4 + 4 = 0
4 = 0

The solution to this equation could not be determined.

See similar equations:

| 12r=18(r+.5) | | -5x+2=10-8x | | r=6(r+.5) | | .3333x+5=.16666(2x-5) | | 12x-3y-10= | | Inx-in(x+3)=6 | | Y/3-y=4 | | 6(2x+4)=8x-3 | | r=6(2r+1) | | -2(3x-1)-4x=5x-(3x-6) | | -12n-(4n+5)=16-3n | | -10-bracket(-7)+2= | | 1/6×5= | | 3/2=3x-4/7 | | -8-(8)= | | 1/6×5 | | y-4x+110=0 | | x^2-9x+y^2=0 | | 7x^2-448= | | r=3(r+.5) | | 11/3×4/9 | | 6-9-(-6)= | | x-2y+74=0 | | 4/9×n=11/3 | | .8=.2+x-0.15 | | 3/100=n/660 | | x+5(x-5)=11 | | 3g+2g+5=0 | | Q^2+16q-15=0 | | 2(3+q)+q=3 | | 4-10-4-(-3)+3= | | an=1+(-1)n |

Equations solver categories